الوعد وتطبيقاته في عقد المرابحة للا مر بالشراء في تمويلات مصرف السلام بالبحرين: دراسة فقهية - بدني, فيصل آدم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research focuses on the topic the doctrine of promise and its practical applications in the Murabahah contract to purchase commodity in financing the case of Al Salam Bank-Bahrain. This study demonstrates the concept of promise and its related words, types, terminologies and other related Islamic banking activities. The study also discusses provisions that are related to the promises and legitimacy of its applications in Islamic Banks, together with the differences in juristic opinion between classical and contemporary scholars. Additionally, it also discusses the body of evidence and states the criteria of legitimacy. Moreover, the study briefly mentiones the Al Salam Bank-Bahrain by stating some of its important internal and foreign policies. The study also concentrates on the concept of the Murabahah contract and its importance, requirements, terminologies and explanation of some contemporary issues in the financing of Al Salam Bank-Bahrain. The study also discusses opinions and decisions of the Shari'ah Board of Al Salam Bank-Bahrain, in the doctrine of promise and the Murabahah, and deals with the explanation and comment on the decisions of its legitimacy. The researcher used an inductive approach in the collection of jurisprudential information from classical and modern sources, and an analytical method where the researcher analyzed the model application of the doctrine of promise with the bank. An evaluation was drawn in light of Islamic jurisprudence and survey method was used to conduct personal interviews with members of the Shari'ah Board of Al Salam Bank-Bahrain. The study found significant results that the doctrine of promise is religiously and judicially compulsory and binding in Islamic Banking and other related financial transactions. The observing of this doctrine is an obligatory requirement in Islamic banking. As such, transactions of Murabahah contract by Al Salam Bank-Bahrain and other Islamic banks are legal and lawful as viewed by contemporary Islamic scholars. Therefore, Al Salam Bank-Bahrain has not violated the Shari'ah provisions in the practical application of doctrine of promise in the Murabahah contract.